BETWEEN OASIS, ISLANDS, AND DESERTS: CROSSING THE WEARINESS. INTERFACES BETWEEN FICTION, LITERATURE, AND SUBJECTIVITY IN MENTAL HEALTH - Madeira, Gabriel Engelman de León; Orofino, Maria Marta Borba (Revista Conhecimento Online: Diversidade e Inclusão Social, 2020)
ABSTRACT This article is a readaptation of the final paper of residency, a fictional product that will be based on the experience lived by the author within the two years of Grupo Hospitalar Conceição, through the art-based research methodology. Working as a means of elaborating learning and experiences carried out in the field and using the metaphor of crossing a desert, the paper is articulated as an imaginative exercise based on experiences and the vision of art as a laboratory for languages, capable of solutions for everyday challenges, expressing silenced affections and discovering unseen elements of the work and teaching institution through contact with its object of interest. Keywords: Subjectivity. Art. Psychoanalysis. Fiction. Mental Health. RESUMO Este artigo é uma readaptação do trabalho final de residência, um produto fictício que será baseado na experiência vivida pelo autor nos dois anos do Grupo Hospitalar Conceição, por meio da metodologia de pesquisa baseada na arte. Trabalhando como meio de elaborar aprendizados e experiências realizadas em campo e utilizando a metáfora de atravessar um deserto, o artigo é articulado como um exercício imaginativo baseado em experiências e na visão da arte como um laboratório de idiomas, capaz de soluções para desafios cotidianos, expressando afetos silenciados e descobrindo elementos invisíveis do trabalho e da instituição de ensino por meio do contato com seu objeto de interesse. Palavras-chave: Subjetividade. Arte. Psicanálise. Ficção. Saúde Mental.